EFFECT OF IRRIGATION AND HYBRIDS ON MICROBIAL POPULATION DYNAMICS IN THE RIZHOSPHERE OF OIL PALM (Elaeis guineensis Jacq.) - Bolanos-carriel, Carlos Andres (Innovare Journal of Agricultural Sciences, 2016)
Objective: This research was carried out to evaluate the effect of irrigation and hybrids on the population dynamics of microorganisms associated with the rhizosphere of oil palm (Elaeis guineensis Jacq.). Methods: Plots were installed under irrigated and non-irrigated conditions using three hybrids (Dura x Pisifera) of oil palm. A split-plot design was used, with three replications. Samples of soil were extracted and processed to determine the populations of functional groups of heterotrophic bacteria, actinomycetes, fungi, phosphorus (P) solubilizing microorganisms, and vesicular arbuscular (VA) mycorrhizae. Samples were taken during the wet season (June) and the dry season (August). Results: No significant differences were detected for bacterial populations (heterotrophic and actinomycetes) for irrigation and hybrids. Populations recorded for heterotrophic bacteria when water stress accounted for 28cbs were 7.43Ã—106 CFU/g (colony forming units per g of dry soil) in irrigated plots, versus 5.86Ã—106 CFU/g in non-irrigated plots. Fungal populations were 4.49Ã—103 CFU/g in irrigated plots, while in non-irrigated plots were 1.81Ã—104 CFU/g. Mycorrhizae levels ranged between 13.6% and 21.9% in irrigated and non-irrigated plots respectively. The populations of P -solubilizing microorganisms ranged from 6.64Ã—105 CFU/g in irrigated plots, to 2.91Ã—104 CFU/g in plots without irrigation. Conclusions: Under the conditions of this study, in the oil palm rhizosphere, there were not significant differences between the bacterial populations (heterotrophs and actinomycetes) for irrigation and hybrids.Â Under the same conditions, significant differences were found among fungal populations, P-solubilizing microorganisms, and VA mycorrhizae, in the irrigation factor. The major bacterial populations were recorded in the rainy season 7centibars (cbs); meanwhile, the higher fungal populations were recorded in the dry season (28cbs). Hybrids not exert major influence on microbial populations under the conditions of this study. With some of the microorganisms isolated in this study, starting tests are needed to identify potential bio â€“ fertilizers, and / or bio â€“ enhancers of soil properties. Â Keywords: VA mycorrhizae, Phosphorus -solubilizing microorganisms, Oil palm, Heterotrophs, Irrigation